Small Border Traffic and Cross-Border Tourism Between Poland and the Kaliningrad Oblast of the Russian Federation - Anisiewicz, Renata; Palmowski, Tadeusz (Quaestiones Geographicae, 2014)
The development of cross-border cooperation, including small border traffic, has not resulted in attracting a substantial number of Polish tourists to the Kaliningrad Oblast, but it has provided such a possibility. This region is quite expensive for the average Pole. However, as scientists from Kaliningrad projected, with the easing of the visa system and the development of transport and tourist infrastructure the role of tourism shows a growing trend.